HUBUNGAN KELENTUKAN TUBUH DAN POWER OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH PADA SISWA KELAS VII SMPN SATAP 5 KAYANGAN TAHUN 2016/2017 - Rosidi, Rosi Rasid; Maulidin, Maulidin; Musrifin, Arif Yanuar (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
The formulation of the problem proposed in this research is whether there is acorrelation between body flexibility and limbs muscle power toward the long jump achievement on the grade VII students of SMPN Satap 5 Kayangan in 2016/2017 academic year. The research objectives were to find out whether or not there is correlation between body flexibility and limbs muscle power toward the long jump achievement on the grade VII students of SMPN Satap 5 Kayangan in 2016/2017 academic year. The design used the product moment correlation. This study is a population study because it used the total population of students of class VII of SMPN Satap 5 Kayangan in 2016/2017 academic year. The form of the test instruments were the body flexibility test and limbs muscle power (independent variable) also the long jump results (dependent variable). The research analysis used multiple correlations, with 5% significance level. The result of calculation obtained that the r score= 0.461, r-table showed that r score is higher than r-table with result of r score = 0.461 and r table with N 32 = 0.394. Finally, it can be concluded that there is correlation between body flexibility and limbs muscle power toward the long jump achievement on the grade VII students of SMPN Satap 5 Kayangan in 2016/2017 academic year